MANAGEMENT OF THE PROGRAM FOR THE FORMATION OF STUDENTS' INDEPENDENCE ATTITUDES - Fahmi, Dede Ropi; Assalam, Sunan Hanif Ihsan; Hariyanto, Teguh (PROCEEDING OF INTERNATIONAL CONFERENCE ON EDUCATION, SOCIETY AND HUMANITY, 2024)
The abstract submitted to this journal should be concise and factual containing the research objectives, the research findings and the main conclusion. It should be presented separately from the article, so it is independent. No more than 250 words, written in both English and Indonesia in one paragraph containing: The research objectives, research methodology, data analysis, and research findings. It is typed using font Book Antiqua (10 pt), single space.